Balancing investments in public service personnel and its healthcare provision output: an efficiency analysis for Brazilian municipalities - Bernardo Furtado (European Regional Science Association (ERSA), 2013)
Brazil has constitutionally adopted a Unified Health System (SUS) since 1988. SUS is designed so that central government, states and municipalities together offer public, free for all full health coverage. The complexity and territorial arrangement of SUS have been developed in such a way that each government body has its specific obligations within the system. This legal framework establishes that the municipalities are competent and responsible for providing basic health attention under general guidance of federal policy. Within this context, the objective of this paper is to estimate how efficiently and under which determinants municipalities? personnel expenses are correlated to increases in health service provision results in the period 2000-2010. In order to do that, firstly, spatial exploratory analysis is applied to data from three different official sources on municipal personnel expenses. The spatial analysis enables insights into the quality of the expenditure information as well as its heterogeneous spatial distribution. The data used is from sampled census individual salary information; mandatory municipal data demanded by the National Treasure and Accountancy Justice Department; and labor social information compiled by the Ministry of Labor that compiles labor social information. Secondly, a Data Envelopment Analysis (DEA) is performed to evaluate comparatively and spatially municipal expenses against health provision indicators. Finally, a regression is fitted to identify which elements suggested in the literature are the most influential on the technical efficiency for the 5,565 Brazilian municipalities. The results confirm (a) that there are high-levels of heterogeneity related to levels of expenditure and basic health achievements; (b) that spatial patterns of efficiency are correlated to economic performance, but also to locally specific relevant differences; (c) and that positive determinants of efficiency are given by: proportion of urban population, family income and family levels of educational background; whereas negative influence is associated to weighted expenses with personnel, small size of municipalities and weighted amount of tax transferences made by the central government. In general, the analysis demonstrates that public provision of services in Brazil is highly heterogeneous. This, in turn, generates cases of local expertise that can be used as benchmarking, but it also makes explicit structural deficiencies that should be specifically tackled by public policy design.
Keywords: 330; municipalities; efficiency; personnel expenses; spatial analysis